Actualizing Sufi Values for the Moral Formation of Qur’an Memorizing Students: A Case Study at Al-Huffaazh, Simalungun - Apriliani, Indri; Syukri, Syukri (Jurnal Pemikiran Islam, 2025)
This study analyzes the actualization of students’ morality through the perspective of Sufism at the Tahfizh Qur’an Al-Huffaazh Foundation in Perdagangan, Simalungun Regency. Utilizing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings demonstrate that the internalization of Sufi values—such as sincerity (ikhlas), patience (sabar), trust in God (tawakkal), and humility (tawadhu)—is authentically manifested in the students’ daily lives through habitual practice, exemplary conduct, and sustained supervision. These values significantly shape students’ character, enhance the quality of Qur’anic memorization, and foster both religious discipline and everyday behavior. Nonetheless, challenges exist, both internal (e.g., peer influence) and external (e.g., gadget usage, social media, and romantic relationships). The foundation has implemented adaptive strategies, including restricting mobile phone usage, optimizing halaqah (group mentoring), individualized guidance, and collaborating with parents to address these issues. The study underscores the urgency of an innovative, collaborative Sufi-based moral education model as a solution for nurturing Qur’anic generations with noble character in the digital era.